Major Sporting Events and National Identification: The Moderating Effect of Emotional Involvement and the Role of the Media. (October 2018) - Mutz, Michael; Gerke, Markus
Research suggests that major sporting events can affect identification with the nation-state. Complementing previous research, it is argued in this article that identification with the national in-group should be enhanced especially among emotionally involved spectators. Emotional involvement, however, can be induced by the sport itself but also by an emotionalized framing of the events by the media. Two studies are presented which test these claims: In Study #1, it is shown that a single, victorious Federation Internationale de Football Association (FIFA) World Cup match suffices to increase national identification among emotionally highly involved subjects, whereas no effects are revealed for individuals with lower emotional involvement. In Study #2, participants reported higher levels of national identification and associated Germany with more positive emotions and values after watching a highly emotional and patriotic broadcast of a kayak competition from the 2016 Summer Olympic Games compared to individuals who had watched the same competition with a factual and neutral commentary. It is concluded from both studies that emotional involvement is a key mechanism through which higher levels of national identification are produced in the realm of sport.